2012
DOI: 10.1111/j.1751-0813.2012.00956.x
|View full text |Cite|
|
Sign up to set email alerts
|

Haematology and biochemistry of warru (Petrogale lateralisMacDonnell Ranges race) in captivity and the wild

Abstract: Objective Use haematology, biochemistry and protein electrophoresis analyses to establish reference values for, and describe the health status of, wild and captive colonies of critically endangered warru (black‐footed rock‐wallaby: Petrogale lateralis MacDonnell Ranges race). Methods Blood samples were taken from warru in three wild colonies (Alalka, Kalka, New Well) in the A nangu Pitjantjatjara Yankunytjatjara Lands in north‐west South Australia (SA) and from captive animals at Monarto Zoo, SA. General haema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
(50 reference statements)
7
19
0
Order By: Relevance
“…Males demonstrated an increasing trend during the lead up 78 to mating between December and February, followed by a low point during peak mating. This finding is consistent with other wildlife studies which have demonstrated that erythrocyte parameters are closely correlated with body condition (Algar et al 1988;Ruykys and McCarthy, 2012).…”
Section: Temporal Variationssupporting
confidence: 83%
See 4 more Smart Citations
“…Males demonstrated an increasing trend during the lead up 78 to mating between December and February, followed by a low point during peak mating. This finding is consistent with other wildlife studies which have demonstrated that erythrocyte parameters are closely correlated with body condition (Algar et al 1988;Ruykys and McCarthy, 2012).…”
Section: Temporal Variationssupporting
confidence: 83%
“…The mean hematologic and plasma biochemistry values and normal adult reference ranges reported here for P. alecto and P. conspicillatus are consistent with previous reports for Pteropus species, with the exception of mean leukocyte, neutrophil and lymphocyte counts (Heard and Whittier 1997;Olsen, 2002;Ruykys et al 2012;Heard and Whittier 1997;Hall et al 2013;ISIS 2014). In some Pteropus species, higher mean total leukocyte counts have been reported, usually associated with a higher mean lymphocyte count than report in P. alecto and P. conspicillatus in this 73 study.…”
supporting
confidence: 79%
See 3 more Smart Citations